2014
DOI: 10.1124/dmd.113.055616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proton Pump Inhibitors on Metformin Pharmacokinetics and Pharmacodynamics

Abstract: As inhibitors of organic cation transporters (OCTs), proton pump inhibitors (PPIs) may affect the plasma levels of metformin, an OCT substrate. We investigated the effects of two PPIs, pantoprazole and rabeprazole, on metformin pharmacokinetics and glucose levels in healthy subjects. In this open, randomized, six-sequence, three-period crossover study, 24 participants were administered metformin, either alone or in combination with pantoprazole or rabeprazole. The plasma concentrations of metformin and serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Intake of metformin in the morning of day 5 was defined as study time 0 h. On days 4 (−22 h) and 5 (+2 h) of each phase, an oral glucose tolerance test (OGTT, 75 g glucose, AccuChek® Dextrose O.G-T., Roche Pharma AG, Germany) was performed in order to determine the pharmacodynamic consequences of the interaction based on previous work using OGTTs as a biomarker of metformin action [e.g., [23][24][25][26]]. The abovementioned evening dose of metformin was administered in order to have a similar study design as previous studies, which investigated metformin pharmacodynamics in healthy volunteers [23][24][25][26]. In phase B, a dose of 200 mg trimethoprim (tablets, Infectotrimet®, Infectopharm Arzneimittel und Consilium GmbH, Germany) was administered additionally p.o.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intake of metformin in the morning of day 5 was defined as study time 0 h. On days 4 (−22 h) and 5 (+2 h) of each phase, an oral glucose tolerance test (OGTT, 75 g glucose, AccuChek® Dextrose O.G-T., Roche Pharma AG, Germany) was performed in order to determine the pharmacodynamic consequences of the interaction based on previous work using OGTTs as a biomarker of metformin action [e.g., [23][24][25][26]]. The abovementioned evening dose of metformin was administered in order to have a similar study design as previous studies, which investigated metformin pharmacodynamics in healthy volunteers [23][24][25][26]. In phase B, a dose of 200 mg trimethoprim (tablets, Infectotrimet®, Infectopharm Arzneimittel und Consilium GmbH, Germany) was administered additionally p.o.…”
Section: Methodsmentioning
confidence: 99%
“…Metformin was administered additionally 12 h prior to the study day due to pharmacodynamic reasons [see "Materials and Methods", [23][24][25][26]. Plasma concentrations at t=0 h were not significantly different (without trimethoprim, 268 ± 129 ng/ml; with trimethoprim, 248±73 ng/ml) indicating a similar carryover of metformin in the two study phases.…”
Section: Effect Of Trimethoprim On the Pharmacokinetics Of Metformin mentioning
confidence: 99%
“…In the example provided in electronic supplementary Table S2, one can see that the mean half-life for metformin when taken with pantoprazole is 3.38 h [24]. However, the accompanying standard deviation of 0.69 further informs the reader that the half-life may be variable between patients.…”
Section: Discussion/conclusion 22 Study Limitations Describing Potentmentioning
confidence: 93%
“…While this difference is very small and unlikely to have much clinical significance, we speculate that it may be due in part to amelioration by PPIs of metformin's gastrointestinal side effects, improving adherence. Alternatively, it may be due to the increase in plasma metformin concentrations with PPI co-administration described previously in healthy volunteers [8,9]. This study has limitations.…”
Section: Figurementioning
confidence: 85%
“…Two recent short term randomized crossover studies in healthy subjects found that co-administration of metformin with PPIs did not appear to alter metformin's effect on glucose homeostasis, but did increase the area under the curve (AUC) of metformin's plasma concentration by approximately 15% [8,9]. The authors hypothesized that the modest increase in metformin plasma concentration might actually be due to inhibition of OCT transporters, which could reduce uptake into the liver and leave more drug in the plasma.…”
Section: Introductionmentioning
confidence: 99%